The Urgency of Gender-Based Counterterrorism Policy Regulation in Indonesia - Milda Istiqomah; Fachrizal Afandi (Sriwijaya Law Review, 2022)
Gender-based counterterrorism in Indonesia still has not yet obtained greater attention from policy stakeholders. The role of women in handling terrorism cases is still lacking and results in the absence of gender sensitivity. This research aims to analyse regulations regarding policies on terrorism that are spread out not only at the level of laws but also at a more technical level of regulations. This research also involves the analysis on the urgency for policy regulation for gender-based counterterrorism. This research combines both legal/juridical-normative research and juridical-empirical/socio-legal research. The results of this research indicate that counterterrorism regulation in Indonesia is still general or gender-neutral. From an institutional perspective, the institutions that handle the criminal act of terrorism, which are the National Counter-Terrorism Agency (BNPT) and Special Detachment 88 for Anti-Terrorism (Densus 88 AT), have not accommodated a gender perspective. Consequently, the involvement of female law enforcement officials is still limited. Further, the issue of “silo mentalities" among these institutions has resulted in partial counterterrorism policies that are issued by each institution. Policy stakeholders should cooperate with other government institutions and increase the involvement of women in counterterrorism strategies to ensure that counterterrorism policies integrate a gender perspective.